2021
DOI: 10.1371/journal.pone.0243291
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes for 7,995 patients with SARS-CoV-2 infection

Abstract: Objective Severe acute respiratory syndrome virus (SARS-CoV-2) has infected millions of people worldwide. Our goal was to identify risk factors associated with admission and disease severity in patients with SARS-CoV-2. Design This was an observational, retrospective study based on real-world data for 7,995 patients with SARS-CoV-2 from a clinical data repository. Setting Yale New Haven Health (YNHH) is a five-hospital academic health system serving a diverse patient population with community and teaching … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 30 publications
6
37
2
Order By: Relevance
“…Second, most patients experienced a pauci- or asymptomatic COVID-19 disease, with only three patients requiring hospitalization, and that their median age was 37 years, much younger than the typical COVID-19 hospitalized patients. Moreover, the female-to-male ratio was high, this being the opposite of what happens in a case series of hospitalized COVID-19 patients ( 51 ). In this context, it should be highlighted that in a recent study by Trimboli et al.…”
Section: Discussioncontrasting
confidence: 56%
“…Second, most patients experienced a pauci- or asymptomatic COVID-19 disease, with only three patients requiring hospitalization, and that their median age was 37 years, much younger than the typical COVID-19 hospitalized patients. Moreover, the female-to-male ratio was high, this being the opposite of what happens in a case series of hospitalized COVID-19 patients ( 51 ). In this context, it should be highlighted that in a recent study by Trimboli et al.…”
Section: Discussioncontrasting
confidence: 56%
“…The performance of these biomarkers, which provide insight into COVID-19 progression as well as predictions of its severity, presented signi cant sex-based differences. In agreement with prior reports [23,24], the percentage of mortality in our sample was of 3.1%. The analysis of the validity of these indicators as prognostic tools of COVID-19 severity was the rst conducted in Ecuador.…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies have shown that Black individuals have had disproportionately higher infection rates, even as some studies indicate that hospital mortality does not vary by race/ethnicity. 11 Our findings highlight that the burden of COVID-19 among Black subpopulations is not just about infection rates but also worse outcomes. The IHR for Hispanic individuals was lower than for White and Black individuals, which was in accordance with previously reported low hospital admission rates .…”
Section: Discussionmentioning
confidence: 70%